Medicinal Uses of Roselle Plant (Hibiscus sabdariffa L.): A Mini Review - PURO, K.; SUNJUKTA, R.; SAMIR, S.; GHATAK, S.; SHAKUNTALA, I.; SEN, A. (Indian Journal of Hill Farming, 2015)
The use of herbal extracts and nutritional supplements either as alternative or complementary medicine for treatment of diseases is well documented in various cultures such as Ayurveda in India and traditional Chinese medicine system. Medicinal plants as natural antimicrobial agents are gaining popularity. Roselle plant (Hibiscus sabdariffa) Linne (Malvaceae) has been used in folk medicine as a diuretic, mild laxative, and treatment for cardiac and nerve diseases. Herein we discussed some of the recent studies on its various activities.